Research on Korean Pharmacopuncture in South Korea since 2007 - Lim, ChungSan (J Pharmacopuncture, 2014)
OBJECTIVES: The purpose of this study was to investigate the current trends in research on pharmacopuncture in Korea since 2007. METHODS: A literature review was performed by using the search engines ‘Science and Technology Society Village’, ‘Korean Studies Information Service System’, ‘National Discovery for Science Leaders’, and ‘Oriental Medicine Advanced Searching Integrated System’ in Korea from January 2007 to December 2013. Searched key words were ‘pharmacopuncture’, ‘herbal acupuncture’, ‘aqua-acupuncture’, and ‘bee venom’. Finally, we selected 457 papers, including Korean experimental studies and clinical studies. Selected papers were classified according to year of publication, type of pharmacopuncture, disease & topic, research type and the publishing journal. RESULTS: One hundred fifty pharmacopunctures were studied in 457 papers. Single compound pharmacopuncture was the most studied pharmacopuncture in experimental studies while animal-based pharmacopuncture was the most studied pharmacopuncture in clinical studies. Bee venom placed first among the various pharmacopunctures, followed by placenta, sweet bee venom, mountain-ginseng, and anti-inflammatory pharmacopunctures. Experimental research on pharmacopuncture has fallen since 2007 when 55 papers were published. However, clinical research has been increasing steadily. In clinical studies, case reports were numerous than randomized clinical trials (RCTs). Musculoskeletal diseases were the most frequently-treated diseases in studies on pharmacopuncture; among the musculoskeletal diseases, rheumatoid arthritis was the most frequently-treated disease in experimental studies and low back pain was the most frequently-treated condition in clinical studies. Since 2007, 45 different journals have published studies on pharmacopuncture, with the Journal of the Korean Acupuncture and Moxibustion Medicine Society having the largest number of papers on pharmacopuncture and the Journal of Pharmacopuncture the second largest number. CONCLUSION: The trends in research on pharmacopuncture published in studies from 2007 to 2013 were similar to those in studies published before 2006. Many studies on pharmacopuncture focused on bee venom and musculoskeletal diseases. Additional studies on diverse types of and indications for pharmacopuncture are needed.